Expectations of parents of hospitalized newborns regarding care. Part I - Bednarek, Anna; Mianowana, Violetta; Jachorek, Małgorzata (Nursing Problems / Problemy Pielęgniarstwa, 2011)
Introduction . Functions and duties which are deciding on the being of professional looking after let the pediatric/neonatal nurse in the comprehensive way accommodate themselves to happening changes in the health care and growing expectations of parents. Aim of the study . The aim of the study was knowledge of expectations of parents of hospitalized newborn babies of professional functions towards the pediatric nurse in the realization chosen. Material and methods . For examining the scope of expectations of parents of hospitalized newborn babies, towards the pediatric nurse they used the method of the diagnostic survey. A research tool which the questionnaire form of the questionnaire form specially constructed for the purposes of the work was applied. With examinations they embraced 115-personal group of parents at two research hospitals in Lublin in 2007 and 2008. Results . Form of the care they would like to receive which parents of hospitalized newborn babies with the division into protective, therapeutic and education tasks concerns the participation of the nurse in performing necessary examinations and treatments above all, for making measurements of different functions of the organism, and only in the second order of the care and acquiring new abilities and the knowledge in the care of the child. Over 50% respondents of parents admitted that from the pediatric nurse they expected mainly performing therapeutic tasks, next protective (46%) and within the scope of the educative function (32%). The majority of respondents thinks, that participation in healing treatments, picking materials up for examinations, performing measurements of the height and the body weight and of bodily functions of the newborn baby these are activities which only a nurse should carry out by the child, as well as they are expressing a view that tasks of this type should not be delegated for parents of newborn babies. Conclusions . Evaluating needs and expectations of parents towards the nurse enables to plan and taking by the institution proper action which will let parents for capturing nursing problem solvers, will encourage for the cooperation and will increase the effectiveness of action protective towards the child. Nursing Topics 2011; 19 (1): 27–33